Rebordering South Asia: Displaced Persons and Urbanization - Wahab, Sharif A.; Ashutosh, Ishan (Annals of the American Association of Geographers, 2022)
This article analyzes displacement in the context of three communities in South Asia: Afghan refugees in Pakistan, Sri Lankan Tamils in India, and Rohingya refugees in Bangladesh. In each of these cases, refugee management emerges out of the complexities of geopolitics and humanitarianism and becomes central to urban questions of the right to move and remain in the city. Drawing on scholarship in the geopolitics of migrant (im)mobilities, refugee studies, and South Asia studies, we argue that displacement threatens the contours of belonging and citizenship across South Asian nation-states. For these reasons, the cities where the displaced live have become the locus of national unbelonging and state violence through entangled forms of securitization and urbanization. In particular, we detail the spatial and socioeconomic segregation of displaced populations in which they are subject to mundane bureaucratic violence and the role that social class plays in navigating the exclusions triggered by displacement. In the cities where the displaced settle, the displaced shape the urban economy, whereas the state applies strategies of spatial control that aim to nationalize urban space while maintaining the refugees as forever displaceable.